Cartografia simbólica da dignidade dos docentes de universidades brasileiras: uma reflexão à luz de Boaventura Sousa Santos - Medeiros, Ana Lucia de (2013)
Studies on human dignity has gained importance in the social sciences, and in particular between those who research the issues-oriented organizations. The provision of higher education in Brazil showed a significant and fast growth through the creation of new courses and educational institutions. On the other hand, the expansion of higher education has led to precarization of faculty relations, both by the increase in working hours, and the devaluation of professor s salaries. The university management has been guided by monoculture of knowledge and scientific rigor, of linear time, the social classification, the dominant scale and the capitalist productivism, in the wake of Western rationality that is the dominant or hegemonic scientific paradigm. The grid of theoretical work was based on studies by Boaventura Sousa Santos, in particular, on the sociology of absences in the sociology of emergences and the ecologies of knowledge. This author seeks to find alternatives to think about a new world starting from the visibility of rich experiences that exist in the present, but for reasons that were discredited indolent, arrogant, and metonymic proleptic. Sousa Santos undertook to develop a new paradigm and also to counter-hegemonic, and from it, to find concrete alternatives while transforming social reality. In light of this thinking, this thesis intended to rethink the concept of dignity and devoted himself to the study of the following research problem: How the dignity of professors in higher education is designed and symbolized in management spaces in brazilian universities? The aim of this study was to analyze how the dignities of professors is designed and symbolized in management spaces in universities. Data were collected by means of fifteen semiestrutuctured interviews with Brazilian universities professors and they were treated by symbolic cartography. The results showed that professors assign as their responsibility to train and develop competent and ethical people to work in the labor market and in society. Achieving this goal depends on the philosophy and management practices adopted and implemented by higher education institutions. The survey results revealed that universities, as organizations are productive, produced absences and presences of dignity from the professors labor relations and production developed in their interior. The presence of dignity of professors was symbolized by the goddess Minerva representing knowledge and righteousness in Greek-Roman culture context. The lack of dignity was symbolized by the figure of Greek mythology called Sísifo, who was condemned by Zeus to hold a meaningless work and emptied in its subjectivities. The data revealed that Minerva became more present in federal universities and universities aimed at the long term, while Sísifo was more present in private colleges geared towards the short term, but the symbol of Minerva no longer represents the aspirations of society. As well as the Sísifo s.